(3NOeGJ eQGbH GdMSGHGJ dShb GdeGd (B:s (3GdeJWdHGJ GdegfjI heTGcd GdeeGQSI GdYedjI aj VhA eYGjjQ GdeQGLYI GdeUQjI hGdOhdjI hGdCeQjcjI (B/s - (3fUQ Ydj, YHO GdhgGHs ((3GdEScfOQjI(B: s (3GdOGQ GdLGeYjI GdLOjOI(B, s, 2001)
(3GdeQGLYI GdMOjKI dMSGHGJ GdTQcGJ GdebjOI HGdHhQUI, GdEJLGgGJ aj eLGdGJ GdeQGLYI GdeJbOeI, JWhQ eSDhdjI eQGbH GdMSGHGJ fMh Shb GdeGd, NOeGJ eQGbH GdMSGHGJ ZjQ GdJbdjOjI dShb GdeGds
Keywords: (3CShGb GdeGds; (3GdHhQUGJs